Boxing injury epidemiology in the Great Britain team: a 5-year surveillance study of medically diagnosed injury incidence and outcome - Loosemore, M.; Lightfoot, J.; Palmer-Green, D.; Gatt, I.; Bilzon, J.; Beardsley, C. (British Journal of Sports Medicine, 2015)
Objectives: There has been no comprehensive injury report of elite-level amateur boxers in competition and training. We reviewed injuries in training and competition in the Great Britain (GB) amateur boxing squad between 2005 and 2009. Methods: Longitudinal, prospective injury surveillance over 5 years of the GB boxing squad from 2005 to 2009. 66 boxers passed through the squad. The location, region affected, description, and the duration of each injury were recorded by the team doctor and team physiotherapist. We recorded whether the injury occurred during competition or training, and also whether it was a new or a recurrent injury. The injury rate during competition was calculated as the number of injuries per 1000 h. Results: More injuries affected the hand than any other body location. This was the case overall, in training and competition individually, and for both new and recurrent injuries. More injuries occurred during training than during competition, and most injuries were new rather than recurrent. Total injury rate during competition was 828 per 1000 h and hand injury rate in competition was 302 injuries per 1000 h. Hand injury rate in competition was significantly higher than at the other locations. The incidence of concussion is comparatively low. Conclusions: Injury prevention should aim to protect the hands and wrists of elite amateur boxers.